Last modified on January 30th, 2025

Reciprocal Identities

Reciprocal identities express the inverse relationships between the six trigonometric functions: sine, cosine, tangent, cosecant, secant, and cotangent.

Formulas

Here are the three basic trigonometric functions, sine, cosine, and tangent, and their relation to their reciprocals:

Sine and Cosec

Sine is the reciprocal of cosec and vice versa.

  • ${\sin \theta =\dfrac{1}{\text{cosec}\, \theta }}$
  • ${\text{cosec}\, \theta =\dfrac{1}{\sin \theta }}$

Cosine and Sec

Cosine is the reciprocal of sec and vice versa.

  • ${\cos \theta =\dfrac{1}{\sec \theta }}$
  • ${\sec \theta =\dfrac{1}{\cos \theta }}$

Tangent and Cotangent

Tangent is the reciprocal of cotangent and vice versa.

  • ${\tan \theta =\dfrac{1}{\cot \theta }}$
  • ${\cot \theta =\dfrac{1}{\tan \theta }}$

Proofs

Here, we will consider a right-angled triangle ABC, which is right-angled at C, to derive the reciprocals.

Sine and Cosec

From the triangle ABC,

sin θ = ${\dfrac{b}{c}}$ = ${\dfrac{Opposite \  side}{Hypotenuse}}$

As we know, 

The reciprocal of ${\dfrac{b}{c}}$ is ${\dfrac{c}{b}}$ 

⇒ ${\dfrac{c}{b}}$ = ${\dfrac{Hypotenuse}{Opposite \  side}}$ = cosec θ

Thus, sin θ is the reciprocal of cosec θ and vice-versa.

Cosine and Sec

Similarly, from the triangle ABC, 

cos θ = ${\dfrac{a}{c}}$ = ${\dfrac{Adjacent \  side}{Hypotenuse}}$

As we know,

The reciprocal of ${\dfrac{a}{c}}$ is ${\dfrac{c}{a}}$

⇒ ${\dfrac{c}{a}}$ = ${\dfrac{Hypotenuse}{Adjacent \  side}}$ = sec θ

Thus, cos θ is the reciprocal of sec θ and vice-versa.

Tangent and Cotangent

Again, from the triangle ABC, 

tan θ = ${\dfrac{b}{a}}$ = ${\dfrac{Opposite \  side}{Adjacent \  side}}$

As we know, 

The reciprocal of ${\dfrac{b}{a}}$ is ${\dfrac{a}{b}}$

⇒ ${\dfrac{a}{b}}$ = ${\dfrac{Adjacent \  side}{Opposite \  side}}$ = cot θ

Thus, tan θ is the reciprocal of cot θ and vice-versa.

Relationship Between Reciprocal Identities

The product of a trigonometric function and its reciprocal is always equal to 1:

  • sin θ × cosec θ = 1
  • cos θ × sec θ = 1
  • tan θ × cot θ = 1

Finding Values Using Reciprocal Identities

Find: cosec θ if sin θ = ${\dfrac{3}{5}}$

As we know, cosec θ is the reciprocal of sin θ

Here, ${\text{cosec}\, \theta =\dfrac{1}{\sin \theta }}$ and sin θ = ${\dfrac{3}{5}}$

Thus, cosec θ = ${\dfrac{5}{3}}$

Find the value of cot 60° if tan 60° = ${\sqrt{3}}$

As we know, cot θ is the reciprocal of tan θ 

Here, cot 60° = ${\dfrac{1}{\tan 60^{\circ }}}$ and tan 60° = ${\sqrt{3}}$

Thus, cot 60° = ${\dfrac{1}{\sqrt{3}}}$

Simplifying Using Reciprocal Identities

The reciprocal trigonometric functions can also be used to simplify complex mathematical expressions.

Simplify: ${\dfrac{\tan \theta \sec \theta }{\cot \theta \text{cosec}\, \theta }}$ 

By expressing the reciprocal functions in terms of sine and cosine, we get

${\sec \theta =\dfrac{1}{\cos \theta }}$, ${\text{cosec}\, \theta =\dfrac{1}{\sin \theta }}$, ${\tan \theta =\dfrac{\sin \theta }{\cos \theta }}$, and ${\cot \theta =\dfrac{\cos \theta }{\sin \theta }}$

Now, by substituting these values into the expression, we get

${\dfrac{\tan \theta \sec \theta }{\cot \theta \text{cosec}\, \theta }}$

= ${\dfrac{\dfrac{\sin \theta }{\cos \theta }\cdot \dfrac{1}{\cos \theta }}{\dfrac{\cos \theta }{\sin \theta }\cdot \dfrac{1}{\sin \theta }}}$

= ${\dfrac{\dfrac{\sin \theta }{\cos ^{2}\theta }}{\dfrac{\cos \theta }{\sin ^{2}\theta }}}$

= ${\dfrac{\sin \theta }{\cos ^{2}\theta }\cdot \dfrac{\sin ^{2}\theta }{\cos \theta }}$

= ${\dfrac{\sin ^{3}\theta }{\cos ^{3}\theta }}$

= ${\tan ^{3}\theta}$

Graphing

On graphing the reciprocal functions, we get

Here

  • The secant function (y = sec θ) is undefined at odd multiples of ${\dfrac{\pi }{2}}$ where cos θ = 0 
  • The cosecant function (y = cosec θ) is undefined at multiples of π where sin θ = 0 
  • The cotangent function (y = cot θ) is also undefined at multiples of π where tan θ = 0

These undefined points correspond to the vertical asymptotes of their respective graphs, as shown.

Solved Examples

Find the values of the following reciprocal trigonometric functions:
a) ${\text{cosec}\, \dfrac{\pi }{4}}$ when ${\sin \dfrac{\pi }{4}=\dfrac{\sqrt{2}}{2}}$
b) ${\sec \dfrac{\pi }{3}}$ when ${\cos \dfrac{\pi }{3}=\dfrac{1}{2}}$
c) ${\tan \dfrac{\pi }{4}}$ when ${\cot \dfrac{\pi }{4}=1}$

Solution:

a) As we know, sine and cosecant are reciprocal functions.
${\text{cosec}\, \theta =\dfrac{1}{\sin \theta }}$
Here, ${\text{cosec}\, \dfrac{\pi }{4}}$
= ${\dfrac{1}{\sin \dfrac{\pi }{4}}}$
= ${\dfrac{1}{\dfrac{\sqrt{2}}{2}}}$
= ${\dfrac{2}{\sqrt{2}}}$
= ${\sqrt{2}}$
Thus, ${\text{cosec}\, \dfrac{\pi }{4}}$ = ${\sqrt{2}}$
b) As we know, cosine and secant are reciprocal functions.
${\sec \theta =\dfrac{1}{\cos \theta }}$
Here, ${\sec \dfrac{\pi }{3}}$
= ${\dfrac{1}{\cos \dfrac{\pi }{3}}}$
= ${\dfrac{1}{\dfrac{1}{2}}}$
= ${2}$
Thus, ${\sec \dfrac{\pi }{3}}$ = ${2}$
c) As we know, tangent and cotangent are reciprocal functions.
${\tan \theta =\dfrac{1}{\cot \theta }}$
Here, ${\tan \dfrac{\pi }{4}}$
= ${\dfrac{1}{\cot \dfrac{\pi }{4}}}$
= ${\dfrac{1}{1}}$
= ${1}$
Thus, ${\tan \dfrac{\pi }{4}}$ = ${1}$

Evaluate: ${\dfrac{\cos \theta }{\sin \theta }\times \text{cosec}\, \theta \times \sec \theta}$

Solution:

Here, ${\dfrac{\cos \theta }{\sin \theta }\times \text{cosec}\, \theta \times \sec \theta}$
= ${\dfrac{\cos \theta }{\sin \theta }\times \dfrac{1}{\sin \theta }\times \dfrac{1}{\cos \theta }}$
= ${\dfrac{1}{\sin \theta }\times \dfrac{1}{\sin \theta }}$
= ${\dfrac{1}{\sin ^{2}\theta }}$
= ${\text{cosec}\, ^{2}\theta}$ 
Thus, ${\dfrac{\cos \theta }{\sin \theta }\times \text{cosec}\, \theta \times \sec \theta}$ = ${\text{cosec}\, ^{2}\theta}$

Prove the identity: cosec2 θ – cot2 θ = 1

Solution:

Here, cosec2 θ – cot2 θ
= ${\dfrac{1}{\sin ^{2}\theta }-\dfrac{\cos ^{2}\theta }{\sin ^{2}\theta }}$
= ${\dfrac{1-\cos ^{2}\theta }{\sin ^{2}\theta }}$
= ${\dfrac{\sin ^{2}\theta }{\sin ^{2}\theta }}$ (From the identity, sin2 θ + cos2 θ = 1)
= ${1}$
Thus, cosec2 θ – cot2 θ = 1, proved.

Simplify the expression: ${\dfrac{\sec ^{2}\theta -\tan ^{2}\theta }{\text{cosec}\, ^{2}\theta -\cot ^{2}\theta }}$

Solution:

Here, ${\dfrac{\sec ^{2}\theta -\tan ^{2}\theta }{\text{cosec}\, ^{2}\theta -\cot ^{2}\theta }}$
Using Pythagorean identities, 1 + tan2 θ = sec2 θ and 1 + cot2 θ = cosec2 θ,
= ${\dfrac{1+\tan ^{2}\theta -\tan ^{2}\theta }{1+\cot ^{2}\theta -\cot ^{2}\theta }}$
= ${\dfrac{1}{1}}$
= ${1}$
Thus, ${\dfrac{\sec ^{2}\theta -\tan ^{2}\theta }{\text{cosec}\, ^{2}\theta -\cot ^{2}\theta }}$ = ${1}$

Last modified on January 30th, 2025